2016
DOI: 10.1093/mnras/stw1796
|View full text |Cite
|
Sign up to set email alerts
|

Chemical enrichment of the pre-solar cloud by supernova dust grains

Abstract: The presence of short-lived radioisotopes (SLRs) in Solar system meteorites has been interpreted as evidence that the Solar system was exposed to a supernova shortly before or during its formation. Yet results from hydrodynamical models of SLR injection into the proto-solar cloud or disc suggest that gas-phase mixing may not be efficient enough to reproduce the observed abundances. As an alternative, we explore the injection of SLRs via dust grains as a way to overcome the mixing barrier. We numerically model … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 108 publications
(177 reference statements)
1
30
1
Order By: Relevance
“…If sustained over the lifetime of the cluster this would mean that the stars would have had unrealistically massive disks (greater than the star's mass) at some point in the past. However, θ 1 Ori C may have switched on only ∼ 10 5 years ago (Scally & Clarke 2001), in which case it is unlikely that the combination of photoevaporation and viscous accretion will have significantly depleted the disks (Garcia 2011). This suggests that the Orion Nebula is in a relativity short-lived stage of its evolution, which is consistent with the lack of proplyd-like objects in other clusters (e.g.…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…If sustained over the lifetime of the cluster this would mean that the stars would have had unrealistically massive disks (greater than the star's mass) at some point in the past. However, θ 1 Ori C may have switched on only ∼ 10 5 years ago (Scally & Clarke 2001), in which case it is unlikely that the combination of photoevaporation and viscous accretion will have significantly depleted the disks (Garcia 2011). This suggests that the Orion Nebula is in a relativity short-lived stage of its evolution, which is consistent with the lack of proplyd-like objects in other clusters (e.g.…”
Section: Introductionmentioning
confidence: 64%
“…It has been suggested (by e.g. Goodson et al 2016) that dust grains would be able to penetrate and be absorbed more easily into the disk. However, the abundance of dust grains in the SNR is uncertain (see e.g.…”
Section: Enrichment Via Supernovamentioning
confidence: 99%
See 2 more Smart Citations
“…Oullette et al (2007Oullette et al ( , 2010 studied SN shock wave injection into the solar nebula, and found that only solid particles larger than ∼ 1 µm can be injected; smaller particles and gas in the SN shock front are unable to penetrate into the much higher density protoplanetary disk. Goodson et al (2016) performed a similar study of particle injection, but into a molecular cloud rather than a disk, and also found that particles larger than ∼ 1 µm were preferentially injected deep with the target cloud. However, analysis of Al and Fe dust grains in SN ejecta constrain their sizes to be less than 0.01 µm (Bocchio et al 2016), effectively severely limiting the value of both of these injection mechanism scenarios.…”
Section: Early Estimates Of the Initial Amount Ofmentioning
confidence: 96%